Economical Silicon Nanowire Growth via Cooling Controlled Solid–Liquid–Solid Mechanism - Thao Nguyen; Chu‐Hsiu Hsu; Der‐Hsien Lien; Yu‐Sheng Su (Advanced Materials Interfaces, 2023)
Abstract Conventional vapor–liquid–solid mechanism of nanowire growth opens up new opportunities of fabricating nanowires with controllable morphologies and aspect ratios. However, gaseous precursors have disadvantages of high material and processing cost, high toxicity, and limited scalability. By contrast, synthesizing nanowires via solid–liquid–solid mechanism could be a facile alternative since the low cost and nontoxic solid precursor is adopted in the process. In this study, the cooling control is found to be very critical for the solid–liquid–solid nanowire growth. Without a sufficient negative vertical temperature gradient, the nucleation and continuous growth of silicon nanowires could not occur. High volume gas flow cooling, fluctuating the heating temperature, decreasing the cooling rate, and applying a heat sink are all efficacious to promote silicon nanowire formation. In addition to the nanowires formed under high gas flow cooling on the silicon wafer sputtered with a nickel thin film, the solid–liquid–solid mechanism‐derived silicon nanowire growth can also be economically achieved by adopting a solution‐based coating of a nickel precursor onto the silicon substrate paired with a programmed slow cooling condition without using any gas, which could be transferred to other eutectic systems for cost‐effective nanomaterial fabrication.